Noção de feminilidade em Melanie Klein: subjetivações para além de um registro fálico - Klipan, Marcos Leandro [UNESP] (2015)
This work intends to understand the theme of femininity changes in the work of Melanie Klein and then trace a historical and epistemological route on the significance of this issue to the thought of this author. Specifically, we also aim to discuss and question how the notion of femininity can offer an innovative way in order to read and understand the Kleinian text. Despite that, we believe that this issue will allow other subjective tracks to come up in contemporary times, what repercussions later in the way of understanding psychoanalysis displaced the phallic trait. In other words, since the beginning of this research we were based on the idea that there would be, as is advocated by some contemporary authors of psychoanalysis and that had been reflected by Freud at the end of his work, the ability to understand modes of subjectivity out of phallic trait i.e. prior to the traditional structure of the Oedipus complex and heritage of our Western culture. Femininity, so it would be this subjectivity so in a very primitive psychic time of the child with his mother, which would allow different subjective joints